PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT SINERGI INTEGRA SERVICES - Dinda Chairani Mantika; Angga Rovita (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of motivation and work environment on job satisfaction. The sample used was a saturated sampling technique, totaling 60 employees. Quantitative research methods. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and f test with the help of the Statistical Product and Service Solution (SPSS) program ). The research results show that: (1) Partially there is a positive and significant influence between motivation on employee job satisfaction, this is proven by the calculated t value of l3.920 > t table 1.67155 with a significance of 0.002 < 0.05. (2) Partially there is a positive and significant influence between the work environment on employee job satisfaction, this is proven by the calculated t value of 3.490 > t table 1.67155 with a significance of 0.000 < 0.05. (3) Simultaneously there is a positive and significant influence between motivation and work environment on job satisfaction, this is proven by the calculated f value of 107.365 > f table 3.159 with a significance level of 0.000 < 0.05.